2005
DOI: 10.1002/cncr.20873
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Muir–Torre syndrome among patients with sebaceous tumors and keratoacanthomas

Abstract: The three‐dimensional architecture of the right ventricular myocardium is a major determinant of function, but as yet no investigator‐independent methods have been used to characterize either the normal or hypertrophied state. We aimed to assess and compare, using diffusion tensor magnetic resonance imaging, the normal architecture with the arrangement induced by chronic hypertrophy. We randomized 20 female 5 kg piglets into pulmonary trunk banding (N = 16) and sham operation (N = 4). Right ventricular hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
94
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(101 citation statements)
references
References 359 publications
(414 reference statements)
2
94
0
3
Order By: Relevance
“…13,21 Briefly, these include studies on patients with Muir-Torre syndrome showing that expression of both MLH-1 and MSH-2 by immunohistochemistry is highly predictive of microsatellite stability (93%) while loss of either is associated with microsatellite instability (100%). 3,4,20 A good correlation between the two methods has been observed in patients with hereditary nonpolyposis colorectal cancer and also in patients with sporadic carcinomas of the colon and the endometrium. 22 In one study of 19 cutaneous tumors from patients with Muir-Torre syndrome and a germline mutation in MLH-1 or MSH-2 by molecular analysis, immunohistochemistry Figure 1.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…13,21 Briefly, these include studies on patients with Muir-Torre syndrome showing that expression of both MLH-1 and MSH-2 by immunohistochemistry is highly predictive of microsatellite stability (93%) while loss of either is associated with microsatellite instability (100%). 3,4,20 A good correlation between the two methods has been observed in patients with hereditary nonpolyposis colorectal cancer and also in patients with sporadic carcinomas of the colon and the endometrium. 22 In one study of 19 cutaneous tumors from patients with Muir-Torre syndrome and a germline mutation in MLH-1 or MSH-2 by molecular analysis, immunohistochemistry Figure 1.…”
Section: Discussionmentioning
confidence: 87%
“…16,17 A clinical diagnosis of this subtype can be made in a patient with concurrent or sequential documentation of a sebaceous neoplasm and a minimum of one internal malignancy or, multiple keratoacanthomas and a visceral malignancy and a positive family history. 3,4,18 The significance of a negative history is perhaps mitigated by reports indicating that patients with Muir-Torre syndrome typically develop their first internal malignancy at an older age. 18 The clinical relevance of identifying patients with an inherited cancer predisposition, necessitates the use of alternative laboratory-based screening methods to identify microsatellite instability or germline mutations in the mismatch repair proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,18,[36][37][38] To our knowledge, only one study has analyzed the expression of all four mismatch repair proteins in skin sebaceous neoplasms (Table 5). 19 Orta et al 19 analyzed 27 patients with one or more sebaceous neoplasms and showed abnormal mismatch repair protein expression in 12 (44%) patients (Table 4).…”
Section: Discussionmentioning
confidence: 99%